Penerapan persamaan linear bentuk dasar pada pembelajaran program linear SMA kelas XI MIPA - Syaiful Yazan; Muhamad Hatta (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This classroom action research aims to enhance the learning’s result of linear program by applying the linear equation of basic forms in XI MIPA 3 students of SMA Negeri 1 Martapura. Futher more, want to see the proccess of instruction, the value results of learning linear program, and the students’ respons. The subject of this research is the class XI MIPA 3 student of SMA Negeri 1 Martapura that consist of 37 students. All the students have received the linear program learning by applying the linear equation of basic forms, became the object of the observations, filled the questionnaire, answered the test of first and second cycle, and some of them being interviewed. The collected data has been analysed descrivtively. The study’s result shows: (1) the enhancement of learning result is 15%, from the average 84,63 at the first cycle, becomes 97,33 at the second cycle, it means the application of the linear equotion of basic forms can enhances the learning result of linear program of XI MIPA 3 student at SMA Negeri 1 Martapura in the lesson year 2015/2016, (2) from the instruction process, indicats that the psychomotor of the students are very good, and (3) the respons of the students to the linear program learning by applying linear equotion of basic forms are in very good catagorized. The respondents hope: (1) the linear equotion of basic forms should be developed, and in the other topics of mathematics and also the other learning subjects could be applying the simple ways, (2) althought the application of linear equotion of basic form is simple, it should be done carefully and following the concept. (3) the teacher should enhance the service to the students by managing the learning’s speed, the using of whiteboard or screen, and give more examples and variated problems, particulary in problem solving.